Problematika Kewilayahan dalam Pengembangan Desa Wisata Kerta - Niken, Niken; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i01.p15, 2021)
Kerta Tourism Village is one of tourism village that located in Bali. This tourism village is still in development stage and has some problems. The problems that arise are the problem that can be solved easily to the problems that can hinder the development of tourism village itself. The common problem is that there is no standardization of tourism village so that their development is irregular and the attraction places is in inappropriate areas and can interfere the territory of the village. Base on this condition, the goal of this research is to find out the problem about the territory problematics that exist in developing Kerta Tourism Village. The research methodology used in this research is qualitative research with qualitative methods. The method are used in-depth interview technique and observation. The technique of determination of informants used is purposive sampling technique. Data sources used are primary and secondary data sources. Primary data in this research is sourced from direct observation to the research location by means of observation and interviews. While secondary data in this research are the dataobtainedfromthedocumentationor studieslibrarytocomplementtheprimarydatafromthelocusoftheresearch. The results of this research showed that the exist problems about territory problematics at Kerta Rural Village are about over function of land, ownership, problematics of garbage and about the spatial rules. Therefore, it is necessary to make rules regarding land ownership and land function, make a warning board not to litter and completing the spatial design. Keyword: Tourism Village, Territory Problematics, Kerta